An overview of psoriatic arthritis including clinical manifestations, assessment, diagnostic criteria, investigations, drug management and GRAPPA guidelines. (10th November 2022) - Packham, Jonathan; Tarar, Bilal
Abstract: Psoriatic arthritis (PsA) is a chronic and often progressive inflammatory disease, occurring in up to 30% of patients with psoriasis. Assessment of patients with PsA requires consideration of all disease domains, including peripheral arthritis, axial disease, enthesitis, dactylitis, skin psoriasis, psoriatic nail disease, uveitis and inflammatory bowel disease. Co‐morbidities and related conditions should all be considered including: obesity, metabolic syndrome, cardiovascular disease, anxiety/depression, liver disease, chronic infections, malignancy, osteoporosis, fibromyalgia and reproductive health.